Answer:
C) 8
Step-by-step explanation:
-5(a+3)=-55
a+3=-55/-5
a+3=11
a=11-3
a=8
Answer:
16yyyy
Step-by-step explanation:
Getting rid of exponents:
- (-2y)^4 =
- (-2)^4*y^4 =
- 16yyyy
You know 1 is not a root because the sum of the coeffcients of the equation is 14, not zero.
It is fairly easy to try 3 by synthetic division (see attachment), which tells you that 3 is a root and the remaining quadratic factor is x²-3x-5. The quadratic formula tells you the roots of that factor are
... x = (-b±√(b²-4ac))/(2a) = (3±√29)/2
The appropriate choices are
... C. (3-√29)/2
... D. (3+√29)/2
... F. 3
_____
The quadratic formula tells you the solution to
... ax²+bx+c=0
is x = (-b±√(b²-4ac))/(2a)
We have a=1, b=-3, c=-5.
Answer:
10
Step-by-step explanation:
(3 + 12) - 3² + 8 · 2 ÷ 4
15 - 9 + 16 : 4
6 + 4
10